SOME ASPECTS OF IMPLEMENTATION OF INTERNATIONAL HUMANITARIAN LAW STANDARDS IN THE FIELD OF CAPTIVITY OF WAR IN RUSSIAN LEGISLATION AT THE PRESENT STAGE - Oleg S. Kiritsa (Russian Studies in Law and Politics)
Issues of legal regulation of military captivity are very relevant. At different times, humanity has experienced many wars and military conflicts, with which came experience and the realization that even during armed confrontation it is necessary to respect the law, show mercy and humanity towards an enemy who is helpless or does not want to fight. The emergence of norms in the field of military captivity in international humanitarian law dictated the necessary desire of countries to implement these norms into national legislation. The rapid development of modern law and legal policy determines the increase in the culture of society, and at the same time the preservation of humanity and respect for the human dignity of prisoners of war. Our country, being a highly developed and rule-of-law state, has always strived to implement the norms of international law in the field of military captivity, both in Soviet and Russian legislation. However, in the history of domestic law to this day, organizational, political and legal problems arise in the implementation of the norms of international humanitarian law relating to military captivity into national legislation. The above problems are a consequence of a complex of social reasons, both objective and private. Continuing research into the dynamics of the process of implementing the norms of international law in the field of military captivity into Russian legislation, a comprehensive study of the issue of legal implementation of the implemented norms will allow us to find ways to solve problems in this area, as well as draw a conclusion regarding the further development of legal norms relating to military captivity in our country.